Peranan Jabatan Kebudayaan, Kesenian dan Warisan Negeri Sarawak dalam memperkembangkan adat resam Masyarakat Melayu Sarawak - Mohammad Fauzi, Ali (Universiti Malaysia Sarawak (UNIMAS), 2006)
This research was conducted to understand the Malay culture which had been practised in Sarawak. The Malay culture in Sarawak can be potentially preserved. The researcher also try to understand the roles and efforts done by Department of Culture. Arts and Heritage Sarawak Country in maintaining. enlarging and sharry the Sarawakian Malay Culture forever.